Radio-loudness Statistics of Quasars from Quaia-VLASS - Nestor Arsenov; Sándor Frey; András Kovács; Lyuba Slavcheva-Mihova (The Astrophysical Journal Supplement Series)
Quasars are objects of high interest in extragalactic astrophysics, cosmology, and astrometry. One of their useful qualities is their potential radio-loudness. However, the fraction of radio-loud versus radio-quiet quasars is subject to ongoing investigations, where the statistical power is limited by the low number of known quasars with radio counterparts. In this analysis, we revisited the radio-loudness statistics of quasars by significantly expanding the pool of known sources. Our main goal was to create a new, value-added quasar catalog with information about their extinction-corrected magnitudes, radio flux density, possible contamination levels, and other flags, besides their sky coordinates and photometric redshifts. We cross-matched the optical Quaia catalog of about 1.3 million quasars (from the Gaia data) with 1.9 million sources from the Very Large Array Sky Survey (VLASS) radio catalog. We explored different thresholds for the matching radius, balancing completeness and purity of the resulting Quaia-VLASS catalog, and found 1 $\mathop{.}\limits^{\unicode{x02033}}$ 5 a sufficient choice. Our main finding is that the quasar radio-loud fraction is in good agreement with previous works (<10%), and there is no significant large-scale sky pattern in radio-loudness. The exact estimate depends on the G -band magnitude limit, and we observed weak trends with redshift and absolute optical magnitude, possibly indicating remnant systematic effects in our data. The crossmatched Quaia-VLASS catalog with 43,650 sources and accompanying codes is available at doi: http://doi.org/10.5281/zenodo.16035690 . This latest census of QSOs with radio counterparts will facilitate further investigations of the dichotomy of radio-loud and radio-quiet quasars, and it may also support other lines of research.